A rhetorical conversation : Jewish discourse in modern Yiddish literature - Finkin, Jordan D., 1976- (The Pennsylvania State University Press, 2010)
"Describes the role of traditional Jewish texts in the development of modern Yiddish literature, as well as the closely related development of modern Hebrew literature"--Provided by publisher